A study on the effects of piston secondary motion in conjunction with clearance joints. (July 2020) - Guo, J.; Randall, R.B.; Borghesani, P.; Smith, W.A.; Haneef, M.D.; Peng, Z.
Highlights: New governing equations of piston secondary motion are developed. The sensitivities of impact responses to joint clearances are different. A critical value, influencing piston impact responses, exists for joint clearance. Abstract: Piston secondary motion caused by the changes in side forces and a clearance between piston skirt and cylinder liner, is inevitable in crank train. Studies reporting the combined effect of the associated joint clearances on piston secondary motion are rare, due to the complexity of analysis involved. This paper presents a dynamic model to analyze piston secondary motion considering all associated joint clearances. In this model, both the reciprocating and secondary motion of piston are considered as well as the planar motion of connecting rod. By adjusting the clearances, and simulating with/without the piston secondary motion, their effects on the dynamics of crank train system are evaluated. The simulated results indicate that the effects of joint clearances are closely connected with the impact responses caused by piston secondary motion. The dynamic model in the paper can be used to find the limit of joint clearance for analysis and design purpose of piston group.